Tropical sapric peat–rubber agglomerates as adsorbent for wastewater treatment - Mohd Asri, Mohd Nawi; Chow, S S; Mohd Zaidi, Ibrahim; Helal Uddin, A.B.M. (SENTRA Academic Publishers, 2008)
Tropical sapric peat soil with severe leaching problems and poor hydraulic conductivities was converted into a functional filter media via heat treatment at 500 °C for 3 hours and agglomerated with natural rubber latex. The optimum weight ratio of peat material to rubber latex was 10:1. The peat-rubber agglomerates (PRA) had improved hydraulic conductivities, neutral pH and low organic leaching. PRA was found to be effective in the removal of chemical oxygen demand (COD) from molasses wastes and domestic wastewater. Adsorption isotherms analysis showed that the uptake of COD by PRA followed both the Langmuir and Freundlich models. Both adsorption and biological processes occurred in the removal of COD. The presence of rubber had improved the rate of bacteria growth on PRA. Sustainable removal of about 80% COD from molasses solution was achieved upon its recycled applications. This self-regenerating characteristics was proven to be due to the growth of bacteria on the surface of the adsorbent.